Crafting Suspense: A Stylistic Analysis of the Girl on the Train - Maryam Ashfaq; Rafia Bilal (Indus Journal of Social Sciences, 2025)
Suspense plays a pivotal role in shaping compelling narratives and has intrigued both literary critics and readers due to its power to hold attention and evoke emotional involvement. In fiction, suspense transcends simple unpredictability; it represents a deliberately crafted emotional journey that evokes anticipation and tension about what is to come. This study explores how suspense is generated and maintained in Paula Hawkins’ novel The Girl on the Train, offering valuable perspectives on narrative craft and the strategic use of language to sustain reader engagement. This research utilizes both qualitative and quantitative methodologies to analyze the selected excerpts from the novel. Drawing on Leech and Short’s (2007) model of stylistic analysis and Carroll’s (1990) theory of suspense, this research examines how linguistic elements and narrative strategies interact to evoke anticipation, uncertainty, and emotional engagement. The analysis of the selected excerpts reveals Hawkins’ strategic use of lexical categories and figures of speech to create a tense and immersive experience. This research demonstrates that suspense in Hawkins’ novel is not solely plot-driven but also intricately woven into linguistic and structural elements, reflecting the protagonist’s fragmented perception of reality. Hawkins’ use of repetition, ambiguity, and vivid imagery aligns seamlessly with Carroll’s parameters of suspense, enhancing readers’ cognitive and emotional engagement. By showcasing how narrative and linguistic techniques synergize, this research contributes to the broader understanding of psychological thrillers and highlights the role of stylistic analysis in contemporary fiction.